Development of Leishmania orientalis in the sand fly Lutzomyia longipalpis (Diptera: Psychodidae) and the biting midge Culicoides soronensis (Diptera: Ceratopogonidae) - Wetpisit Chanmol (2019)
© 2019 Elsevier B.V. Leishmania (Mundinia) orientalis is a newly described species causing human leishmaniasis in Thailand whose natural vector is unknown. L. orientalis infections in sand flies and/or biting midges under laboratory conditions have not been previously investigated. In this study, the development of L. orientalis in two experimental vectors, Lutzomyia longipalpis sand flies and Culicoides sonorensis biting midges was investigated for the first time using light microscopy, scanning electron microscopy, and histological examination. The results showed that L. orientalis was unable to establish infection in Lu. longipalpis. No parasites were found in the sand fly gut 4 days post-infected blood meal (PIBM). In contrast, the parasite successfully established infection in C. sonorensis. The parasites differentiated from amastigotes to procyclic promastigotes in the abdominal midgut (AMG) on day 1 PIBM. On day 2 PIBM, nectomonad promastigotes were observed in the AMG and migrated to the thoracic midgut (TMG). Leptomonad promastigotes appeared at the TMG on day 3 PIBM. Clusters of leptomonad promastigotes and metacyclic promastigotes colonized around the stomodeal valve with the accumulation of a promastigote secretory gel-like material from day 3 PIBM onwards. Haptomonad-like promastigotes were observed from day 5 PIBM, and the proportion of metacyclic promastigotes reached 23% on day 7 PIBM. The results suggest that biting midges or other sand fly genera or species might be vectors of L. orientalis.